Improving Mathayom 2/2 Student Learning Interest in Cell Materials Using Augmented Reality (AR) in Streesmutprakan School, Samut Prakan Province, Thailand - Amala Sholeha Apridza; Erlia Narulita; Anusorn Kongsawang (BIOEDUKASI, 2018)
This study aimed to describe the use of media Augmented Reality (AR) to improve learning interest in Matayom 2/2 class students who are lower secondary grades at Streesmutprakan School. This was a classroom action research (CAR) consisting of two cycles. Each cycle consists of planning stage, acting, observing and reflecting stage. The subjects of this study were all 34 students of Matayom 2/2 class. Data collection techniques included observation, interviews, and documentary analysis. Data analysis techniques used qualitative descriptive analysis. The results showed that students' learning interest in the first cycle was 3.3 with medium criteria, increasing to 4.4 with high criteria in the second cycle. The use of media Augmented Reality (AR) can increase students learning interest in Matayom 2/2 at Streesmutprakan School, Samut Prakan Province, Thailand. Keywords: Augmented Reality, Cell Material, 3D Media, Learning Interest.